1992
DOI: 10.1073/pnas.89.16.7708
|View full text |Cite
|
Sign up to set email alerts
|

Selective expression of interleukin 10, interferon gamma, and granulocyte-macrophage colony-stimulating factor in ovarian cancer biopsies.

Abstract: The variable clinical response seen with most cancer immunotherapy suggests that there is a large interindividual variation in immunologic response to tumors. One of the key functional parameters of an immune response is the local production of cytokines. As a method to survey the immune status of tumor-infiltrating cells, we have investigated the constitutive expression of cytokine mRNA in biopsies from epithelial ovarian carcinomas by using a PCR-assisted mRNA amplification assay. Using a set of cytokine-spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
99
1
3

Year Published

1994
1994
2002
2002

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 215 publications
(118 citation statements)
references
References 32 publications
(19 reference statements)
14
99
1
3
Order By: Relevance
“…Possibly, appropriate stimulation may lead to IL-10 expression by human keratinocytes as well. Interestingly, selective expresssion of IL-10 mRNA has also been found in ovarian tumours but not in normal ovaries and ovarian tumour cell lines (Pisa et al, 1992). Moreover, our results are in line with recent published PCR data on the comparison of cytokine profiles in another malignant tumour of the skin, namely basal cell carcinoma, to that of seborrhoeic keratosis, a benign hyperplasia of epidermis (Yamamura et al, 1993).…”
Section: Specimenssupporting
confidence: 80%
“…Possibly, appropriate stimulation may lead to IL-10 expression by human keratinocytes as well. Interestingly, selective expresssion of IL-10 mRNA has also been found in ovarian tumours but not in normal ovaries and ovarian tumour cell lines (Pisa et al, 1992). Moreover, our results are in line with recent published PCR data on the comparison of cytokine profiles in another malignant tumour of the skin, namely basal cell carcinoma, to that of seborrhoeic keratosis, a benign hyperplasia of epidermis (Yamamura et al, 1993).…”
Section: Specimenssupporting
confidence: 80%
“…It may be concluded from the concomitantly high levels of IL-10 mRNA and IFN-γ mRNA in CD8 + TIL that Th1 as well as Th2 lymphocytes are activated, which is in accordance with a recently published study showing also high levels of IL-10 and IFN-γ mRNA in TIL from non-small cell lung cancer and ovarian cancer biopsies (Asselin-Paturel et al, 1998;Pisa et al, 1992). Since it has recently been shown that in vitro activated T cells express high levels of FasL mRNA and protein (Alderson et al, 1995;Brunner et al, 1995;Dhein et al, 1995;Martinez-Lorenzo et al, 1996), the elevated FasL mRNA levels in RCC TIL also indicate an immunological activation of these lymphocytes.…”
Section: Discussionsupporting
confidence: 90%
“…The CD95 probe was a PCR-amplified 337 bp fragment of the 3 0 region of the CD95 gene (Oehm et al, 1992), radioactively labelled with activities of 4-8 × 10 8 /mg by random priming using the ready prime kit (Amersham Buchler, Braunschweig, Germany). As a control for sample loading and RNA integrity, the Northern blots were reprobed with a [a-32 P]dCTP-labelled probe of the human b-actin gene (Pisa et al, 1992).…”
Section: Methodsmentioning
confidence: 99%